The organizational climate and work motivation of the staff of the I.E. Empire of Tahuantinsuyo 3049 Independence, Lima, 2016 - Zulema Ybela , Antón Estela; Cañamero Tuanama , Nancy Isabel; Cardenas Saavedra, Abraham (Revista Iberoamericana de educación, 2021)
The objective of this work was to determine the degree of relationship that exists between the “Organizational Climate and Work Motivation of the staff of the I.E. Empire of the Tahuantinsuyo 3049 Independence 2016 ”. The research developed is basic, a non-experimental, transactional design was used with a population of 120 collaborators, the degree of reliability is 0.966 for the organizational climate variable composed of 40 items and for the work motivation variable it was 0.889 variable composed of 30 articles. To measure the study variable, the questionnaire was used as an instrument, which was duly validated and applied. The research was developed under a quantitative approach, the hypothetical deductive method of investigation was used. The results show that the degree of relationship is moderate between organizational climate and work motivation where the result of the Spearman correlation was 0.591, in the I.E. Tahuantinsuyo Empire N ° 3049 Independence 2016 (r = 0.591 and p = 0.000).key words: Organizational climate, Work motivation